PEMBERIAN POC GAMAL TERHADAP PERTUMBUHAN DAN PRODUKSI PADI SAWAH (Oryza sativa L.) DENGAN METODE SALIBU - Mamentu, Mifta; Paulus, Jeanne M.; Lengkong, Edy (Universitas Sam Ratulangi, 2018)
ABSTRACT The purpose of the research was to studied the application of gliricidia MOL on the growth and yield of lowland rice in the salibu method, and to get the best concentration of gliricidia liquid organic fertilizer (POC) on the growth and production of lowland rice. Field research has been conducted in Tababo Village, Subdistrict of Belang, district of Southeast Minahasa. The treatment in the experiment consists of one treatment factor, that were concentrations of gliricidia POC, ie : 0, 50 , 100, 150, and 200 ml/litre. The results showed that gliricidia POC have an effect on plant height, the number of grain/panicle, and the dry grain yield (GKP) / plot, but not affect the number of productive tillers and weight of 1,000 grain. The best results were achieved in gliricidia POC concentration 200 ml/litre with the highest values were: plant height was 98.93 cm; 116.420 grain/panicle; and 8.300 kg dry grain yield or equivalent to 6.92 ton/ha.Keywords : gliricidia POC, production, lowland rice, salibu method